2022
DOI: 10.3390/cancers14041046
|View full text |Cite
|
Sign up to set email alerts
|

Robotic Surgery for Biliary Tract Cancer

Abstract: Biliary tract cancer consists of cholangiocarcinoma (CC) and gallbladder cancer (GBC). When resectable, surgery provides the best chance at long-term survival. Unfortunately, surgery for these tumors is associated with long operative times, high morbidities, and prolonged hospital stays. Minimally invasive surgery has been shown to impact selected outcomes, including length of stay, in other diseases, and robotic surgery may offer additional advantages compared to laparoscopic surgery in treating bile duct can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Although some laparoscopic surgeries such as laparoscopic pancreaticoduodenectomy can be almost perfectly performed by specialized hepatobiliary and pancreatic centers, robotic-assisted surgery has pronounced advantages in small space operations when performing pancreaticojejunostomy, bile duct reconstruction and blood vessel reconstruction, etc. (14)(15)(16). Meanwhile, it is undeniable that robotic surgery has a relatively higher cost, which should be taken into reasonable consideration because the paid price also covers the cost of the development of medical science and technological equipment.…”
Section: The Latest International Expert Consensus On Minimallymentioning
confidence: 99%
“…Although some laparoscopic surgeries such as laparoscopic pancreaticoduodenectomy can be almost perfectly performed by specialized hepatobiliary and pancreatic centers, robotic-assisted surgery has pronounced advantages in small space operations when performing pancreaticojejunostomy, bile duct reconstruction and blood vessel reconstruction, etc. (14)(15)(16). Meanwhile, it is undeniable that robotic surgery has a relatively higher cost, which should be taken into reasonable consideration because the paid price also covers the cost of the development of medical science and technological equipment.…”
Section: The Latest International Expert Consensus On Minimallymentioning
confidence: 99%
“…Author details 1 Department of Oncology, Changxing People's Hospital, Huzhou 313100, Zhejiang, China. 2 Department of Hepatobiliary Surgery, Changxing People's Hospital, Huzhou 313100, Zhejiang, China. Zhang and Yao World Journal of Surgical Oncology (2022) 20:320…”
Section: Supplementary Informationmentioning
confidence: 99%
“…Biliary tract cancers (BTCs) comprise a heterogeneous group of aggressive malignancies involving the bile ducts and gallbladder [1]. BTC accounts for approximately 3% of all gastrointestinal malignancies and is the second most common primary hepatic malignancy after hepatocellular carcinoma [2]. BTC comprises intrahepatic cholangiocarcinoma (ICC), extrahepatic cholangiocarcinoma (ECC), and gallbladder cancer (GBC) [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Needless to say, biology trumps technique, and for surgeries that can be done minimally invasively there is a future. Certainly, an ever-increasing number of gallbladder cancers are being addressed minimally invasively, and our recent review has concluded that robotic surgery for biliary tract cancer appears non-inferior to open surgery when compared to published contemporary data ( 4 ).…”
mentioning
confidence: 98%